Transformasi Digital dan Inovasi Produk sebagai Penentu Keberhasilan UMKM Industri Kreatif - Pantja Sudarwanto; Rizky Pribadi (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2026)
Digital transformation and product innovation are increasingly recognized as key factors in determining the success of Micro, Small, and Medium Enterprises (MSMEs), especially in the creative industry sector based on ideas, creativity, and product differentiation. However, empirical findings related to the role of the two factors are still scattered and have not been systematically integrated. This research aims to review and synthesize scientific evidence regarding the influence of digital transformation and product innovation on the success of creative industry MSMEs. The method used is a mild Systematic Literature Review (SLR) with reference to the guidelines of Kitchenham and Charters (2007) and Tranfield et al. (2003). The literature search process was carried out on the Google Scholar and Scopus databases with the inclusion criteria of indexed journal articles, relevant to creative industry MSMEs, and published in the last ten years. Data analysis was carried out thematically to identify the main findings patterns. The results of the study show that digital transformation plays a significant role in expanding market access, increasing operational efficiency, and strengthening the competitiveness of MSMEs, while product innovation contributes to creating differentiation, added value, and business sustainability. These findings confirm that the success of creative industry MSMEs is highly determined by the synergy between the adoption of digital technology and the ability to innovate. This research provides conceptual contributions to the development of MSME literature as well as practical implications for the formulation of policies and strategies for the development of MSMEs based on the creative economy.